Training Methods for Students-Foreigners with the English Level Lower than A1 - Koval, Natalia; Tsapenko, Ludmila; Kokkina, Lilita; Borisenko, Tetyana; Gvozd, Olga; Dobrovolska, Yuliana (Journal of Ecohumanism, 2024)
The English language level of students-foreigners who are going to study at Ukrainian Universities plays a crucial role especially in the cases when their future practical lessons and lectures are delivered in English. The group of Turkish students who had to undergo the training in Medical University as future doctors demonstrated during the preliminary linguistic tests that English (and Ukrainian) knowledge of the majority of students was even lower than A1 level. The causes were as follows: the low level of school education, geographical position of their native places, i.e. their remoteness from the cultural centers of the country, age (the younger the worse) and others. The situation made the Ukrainian teachers, who were responsible for their English training, use some uncommon methods, which should have led to positive results. The methods are as follows: first of all to brake the opposition “teacher – students” which allows to put teachers and students in the same social position; to forbid the use of computer translator during the lessons except for learning the new lexis to stop the irresponsible attitude of students to classes; to control psychological situation during the training and follow the University psychologists advices. The results of such methods use are described in the presented article.